Effect of electron irradiation on excess conductivity of single Y₁Ba₂Cu₃O₇₋δ crystals - Azarenkov, N.A.; Voevodin, V.N.; Vovk, R.V.; Vovk, S.R.; Khadzhai, G.Ya.; Sklyar, V.V. (Functional Materials, 2018)
Effect of electron irradiation on the excess conductivity of Y₁Ba₂Cu₃O₇₋δ single crystals is investigated. It is shown that irradiation with electrons leads to significant expansion of the temperature interval that excess conductivity exists. The excess conductivity Δσ(T) has been revealed to obey an exponential temperature dependence in he broad temperature range Tf < T < T*. The description of the excess conductivity can be interpreted in terms of the mean-field theory where T* is the mean-field ransition temperature to the pseudogap state and Δ*(T) is satisfactory described within the framework of the BCS-BEC crossover heory. The value of the transverse coherence length ξc(0) increases by a factor of 1.4 and the point of 2D-3D crossover shifts with respect to temperature.